A qualitative study investigating the meaning of participation to improve the measurement of this construct. - de Wind, Astrid; van der Beek, Allard J.; Boezeman, Edwin J.; Swenneker, Rosalie; Anema, Johannes R.; de Boer, Angela G. E. M.; Beckerman, Heleen; Hoving, Jan L.; Nieuwenhuijsen, Karen; Scharn, Micky; Stam, Mariska; Terwee, Caroline B.; et al. (Quality of Life Research, 2019)
Purpose: The purpose of this study was to improve the measurement of participation. Research questions were as follows: (1) What constitutes participation according to adults? (2) Do they mention participation subdomains that are not covered in the Patient-Reported Outcomes Measurement Information System (PROMIS) item bank "Ability to Participate in Social Roles and Activities"?Methods: Semi-structured interviews were conducted with 46 adults from the general population. Interviews were thematically analysed using the International Classification of Functioning, Disability and Health (ICF) as conceptual framework. Thereafter, assigned codes were compared to PROMIS item bank.Results: Participants mentioned a variety of participation subdomains that were meaningful to them, such as socializing and employment. All subdomains could be classified into the ICF. The following subdomains were not covered by the PROMIS item bank: acquisition of necessities, education life, economic life, community life, and religion and spirituality. Also a distinction between remunerative (i.e. paid) and non-remunerative (i.e. unpaid) employment, and domestic life was missing. Several ICF sub-codes were not mentioned, such as ceremonies.Conclusions: Many participation subdomains were mentioned to be meaningful. As several of these subdomains are not covered in the PROMIS item bank, it may benefit from extension with new (patient-)reported subdomains of participation.